Coastal Observation Using a Vertical Profiling System at the Southern Coast of Korea - Park, Young-Gyu; Seo, Seongbong; Kim, Dong Guk; Noh, Joocheul; Park, Hyuk Min (Frontiers in Marine Science, 2021)
At a coastal station near the southern coast of Korea, the vertical profiles of temperature salinity dissolved oxygen and velocity were obtained using a vertical profiler, Aqualog, every summer from 2016 to 2020. At the site, fishing activity was not allowed, and it was possible to maintain the profiler continuously and stably. It was set to travel every one or 2 h for two to 4 months. Thus, we were able to observe the variations of the water properties from hourly to monthly scales. The sensors were contaminated much less than we expected, and the data could be used without correction at least for our coastal applications. The main phenomena we observed are tides, coastal warming, fresh water, and responses to typhoons. On the daily time scale, the most prominent phenomenon is semi-diurnal tides, with which the thickness and temperature of coastal warm waters changed. The warm water also showed fluctuations between 10 and 15 days. The data also revealed that the tide showed strong seasonality. In summer, when the water is strongly stratified, the tidal current is baroclinic, while in winter, when the water is well mixed, the current is barotropic. Responses to typhoon induced winds were rather complicated. In one case, increase in the upper mixed layer was observed. The thick mixed layer disappeared in about a day due to advection. In another case the upper mixed layer became thinner, while the wind became stronger due the advection of the offshore water. Hydrographic observations conducted every 2 months, of course, or point measurement at a surface buoy could not show such continuous changes. More and more local fishermen are showing interest in oceanographic information, and data from the profiler could be of much use to them.